PKAN hiPS-Derived Astrocytes Show Impairment of Endosomal Trafficking: A Potential Mechanism Underlying Iron Accumulation - Ripamonti, Maddalena; Santambrogio, Paolo; Racchetti, Gabriella; Cozzi, Anna; Di Meo, Ivano; Tiranti, Valeria; Levi, Sonia (Frontiers in Cellular Neuroscience, 2022)
PKAN disease is caused by mutations in PANK2 gene, encoding pantothenate kinase 2, a key enzyme on Coenzyme A (CoA) biosynthetic chain reactions. This disorder is characterized by progressive neurodegeneration and excessive iron deposition in the brain. The pathogenic mechanisms of PKAN are still unclear, and the available therapies are only symptomatic. Although iron accumulation is a hallmark of PKAN, its relationship with CoA dysfunction is not clear. We have previously developed iPS-derived astrocytes from PKAN patients, showing iron overload thus recapitulating the human phenotype. In this work, we compared PKAN derived astrocytes to those derived from healthy subjects. PKAN astrocytes showed an increase in transferrin uptake, a key route for cellular iron intake via Transferrin Receptor mediated endocytosis of Transferrin-bound iron. Investigation of constitutive exo-endocytosis and vesicular dynamics, exploiting the activity-enriching biosensor SynaptoZip, led to the finding of a general impairment in constitutive endosomal trafficking in PKAN astrocytes. CoA and 4-Phenylbutyric Acid treatments were found to be effective in partially rescuing the aberrant vesicular behaviour and iron intake. Our results demonstrate that impairment of CoA biosynthesis could interfere with pivotal intracellular mechanisms involved in membrane fusions and vesicular trafficking, leading to an aberrant transferrin receptor-mediated iron uptake.